Sistem Pendukung Keputusan Pemilihan Siswa Study Tour Menggunakan Metode TOPSIS - Muhammad Zen; Supiyandi Supiyandi; Chairul Rizal; Sayuti Rahman; Irwan Irwan (STMIK Budi Darma, 2022)
Study tour activities are as a means of learning while recreation for teachers, students and course administrators. This recreational trip while studying is held every year and requires good preparation. For students who wish to take part in the study tour, a selection stage is carried out. In this study, the selection used a decision support system using the TOPSIS method (Technique For Others Reference by Similarity to Ideal Solution). This method consists of several steps that are easy to implement. In this method, there is no special calculation for weights. The weight is determined based on the analysis of all parties involved in developing the system. This system is expected to be able to select students properly through the attributes used, namely achievement, health, files and budget capabilities. Some assessments are carried out by interviews conducted by the course admin. The data is then processed as input to a decision support system. The system was developed using the PHP programming language and MySQL database. Some of the features or menus contained in it are home, alternative data, ratings, rankings and weights. These features are designed so that the system is easy to use. This research resulted in a selection system that makes it easier for administrators to determine students who take part in the study tour. Decision support systems simplify student data collection and topsis method calculations. The value of each criterion can be calculated quickly by the system. The weight used can be changed through the system. Recommendations for students to take part in the study tour can be seen in the ranking menu in the system in order. The system can be used annually in selecting study tour students